Human-livestock interactions [ the stockperson and the productivity and welfare of intensively farmed animals - Hemsworth, Paul H.; Coleman, Grahame J. (CABI, 2010)
Human-animal interactions have a profound effect on farm animals and stockpeople alike. Training of stockpeople can improve livestock welfare and in turn productivity, and is a principle area of focus after improvements in genetics, nutrition, reproduction, health and housing have been addressed extensively. This volume explores new information on human-livestock relationships, their effects on both animals and handlers and the application of this knowledge particularly in relation to dairy cows, veal calves and poultry. Developments in knowledge of the relationships and their effects post-farm gate are discussed, providing a practical guide that will be a valuable resource for farm managers, researchers in the animal sciences, psychologists, ethologists and veterinarians. It will also benefit students of veterinary and animal sciences.